Successful treatment of primary refractory DLBCL/HGBL - MYC/BCL2 transformed from FL using glofitamab: a case report - Chu, Ming-qiang; Zhang, Ting-juan; Feng, Yuan; Shao, Xun; Ji, Yong-hui; Qian, Jun; Zhou, Jing-dong (Frontiers in Immunology, 2025)
Diffuse large B-cell lymphoma/high-grade B-cell lymphoma with MYC and BCL2 rearrangements (DLBCL/HGBL-MYC/BCL2) represents a distinct entity of mature aggressive B-cell lymphoma, constituting a substantial gap in the clinical management of DLBCL. Conventional R-CHOP-like chemoimmunotherapy regimens have demonstrated limited efficacy in DLBCL/HGBL-MYC/BCL2, and the clinical outcome remains poor, with a median overall survival of less than 2 years, and even shorter in cases transformed from indolent lymphoma. We reported a 66-year-old female was firstly diagnosed with follicular lymphoma, but presented with disease progression to DLBCL/HGBL-MYC/BCL2 during the treatment with BR regimen. Moreover, the patient was also primary refractory to Pola-R-CHP. The patient achieved partial response following treatment with the CD20×CD3 bispecific antibody glofitamab and maintained long-term remission. Although only one successful case is presented, glofitamab could be considered as salvage therapy for transformed relapsed/refractory DLBCL/HGBL-MYC/BCL2.